2015
DOI: 10.2113/econgeo.110.6.1485
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Skarn-Hosted Rare-Metal Mineralization in the Ambohimirahavavy Alkaline Complex, Madagascar

Abstract: The Cenozoic Ambohimirahavavy alkaline complex in Madagascar consists of several syenitic to granitic intrusions (24.2 ± 0.6 Ma) the largest of which, the Ampasibitika intrusion, is characterized by the presence in its outer flanks of late peralkaline granitic dikes intruding mudstone and limestone of the Isalo Group. A network of dikelets and veinlets propagates from these dikes, intruding along bedding or obliquely to bedding. At the contact between the dikes and dikelets and a limestone, a reaction zone enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 52 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…We did not obtain data for skarn deposits in this study; however, one published study (Estrade et al, 2015) reported data for 52 FIAs from a rare metal skarn. The data show Th for individual FIAs that range from 1° to 119°C, with a median range of 22.5°C.…”
Section: Skarnsmentioning
confidence: 93%
“…We did not obtain data for skarn deposits in this study; however, one published study (Estrade et al, 2015) reported data for 52 FIAs from a rare metal skarn. The data show Th for individual FIAs that range from 1° to 119°C, with a median range of 22.5°C.…”
Section: Skarnsmentioning
confidence: 93%
“…In the Ambohimirahavavy complex, we have shown in a previous paper that an orthomagmatic fluid exsolved from the melt at a late stage of crystallization of the peralkaline dykes (Estrade et al, 2015). The interstitial texture of EGM indicates that favorable conditions for its crystallization, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…contain sodic clinopyroxene and sodic amphibole) and by the presence of minerals rich in HFSE and REE . Their local intrusion in limestone resulted in the formation of a REE -rich skarn (Estrade et al , 2015).
Fig.
…”
Section: Geological Setting and Petrographymentioning
confidence: 99%
“…Two IAD profiles from the Ambohimirahavavy Alkaline Complex, NW Madagascar, were used as a source of microorganisms [21]. Samples were collected from an IAD profile overlying volcanic breccia within an alkaline ring dyke (sample intervals were 0-0.8 m, 0.8-3.8 m, 3.8-4.8 m and 4.8-5.8 m) and from a profile overlaying the country rock outside the ring dyke (sample intervals 0.9-1.1 m, 3.4-3.6 m, 4.3-4.5 m and 5.8-6.0 m).…”
Section: Methodsmentioning
confidence: 99%